Study of bladder release agent formulas and methods to evaluate their efficiencies by using reciprocating tribometer - N Tanboriphan; B Teeraprawatekul; S Mahathanabodee; I Jangchud (My University, 2022)
Abstract Bladder is one of the most important components in tire manufacturing process. In tire industry, methods to prolong bladder service-life and good bladder coatings for non-stick surface has been acquired. Bladder coated with good release agents can help reducing nonconforming products and increasing production efficiency. In this work, semi-permanent release agent formulas were studied. A new method to evaluate release agent efficiency by using a reciprocating tribometer were also carried out. Polydimethyl siloxane (PDMS) release agent formulas were developed with and without polymethyl hydrogen siloxane (PMHS). Effects of metal salt cure catalyst were also studied. In this work, method of release efficiency test was developed by using a reciprocating tribometer according to ASTM G133-05. It can be used to determine coefficient of friction of the coated surface and durability of the coatings. Coating durability test was also confirmed by repeating compression molding test to determine the number of release cycles. It was found that film durability was improved by adding the metal salt catalyst and PMHS. As the PMHS loading was increased, film endurance was improved to an optimum loading. Friction coefficient of the coatings could be related to the mold release ability and durability of the release agents. The technique can be used to estimate the service-life of the coated bladders. It can be used as a guideline for development of mold release agents in tire manufacturing industry.
Keywords: Tribometer; Reciprocating motion; Service life; Siloxane; Tribology and Wear Analysis